Post election violence and political accomodation in Africa: the case of Kenya and Zimbabwe - Tamum, Divine Chi (My University, 2011)
A cursory look at the resort to power-sharing deals after last elections in Kenya and Zimbabwe, expose as problematic the view that elections in essence are part of a democratic role to resolve political rivalry through non violent means. This report takes a preliminary argument that the resort to power-sharing after disputed elections defeats the ends of electoral democracy and may create a precedent in Africa where incumbent leaders may refuse to vacate office after being defeated in the hope of sharing power with their adversaries; retaining the all powerful presidency. The report further investigates through a comparative analysis the factors that facilitated electoral violence and post election accommodation in both cases, exposing the loopholes of each deal and also introduces electoral violence as the newest approach to power-sharing. The report sums-up with a catalogue of recommendations that could be used to avert similar occurrences elsewhere